Representações identitárias de consumidores em publicidade de cerveja na TV (um estudo de caso das marcas Antarctica, Brahma e Skol) - Neves, Fabiana Nogueira (Universidade Federal de Juiz de Fora (UFJF), 2011)
This dissertation was taken from three assumptions: the centrality that media, especially television, acquired as a provider of identity models to contemporary subjects; the social consumption significance and publicity as its mediator, on production halo. In focus is beer market. The main aim of this research is analyze the identity representation build up on and from market publicity productions of top beer brands in Brazilian market: Skol, Brahma, and Antatctica, all from AmBev. Together these brands concentre more than 70% on Brazilian market. These representations were studied through the identification of creative and discursive strategies present on market publicity productions of each brand; we started from the positioning - the image that the market publicity production try to project on consumer – expressed on each campaign. Thereafter we tried to inferred, from the series of tangible attributes and, mainly, from intangible attributes linked to the brands, the possible identity conformations build up for its consumer from advertising discourse. The market publicity productions chosen were: "Boa, só se for Antarctica”, “Brahmeiros” e “Tá na roda? Tá redondo!”, which advertisements were exhibited on free TV between 2006 and 2009. A sum of twenty eight films are being studied using semiotic principles and historic contextualization as methods of analysis. Combining a brief study of signs with a second one, related to the social context in which the brand is inserted, the analysis try to offer explanations that make clear the manner (or manners) through publicity proposes identity prototypes for the hypermodern subject. The analysis allowed us verify that the brands try to cover themselves in a identity builded up on the most expensive values for its consumer, to afterwards, through the magic discourse of publicity communication, taken them back transformed, improved, by the product consumption bond. The product/brand, inserted on social practices predominantly associated to pleasure and leisure, act as ...